Benefits Of Ratification Of The Madrid Protocol (Protocol Relating To The Madrid Agreement Concerning The International Registration Of Marks) For The Protection Of Intellectual Property Rights In Indonesia - Risti Dwi Ramasari (International Conference On Law, Business and Governance (ICon-LBG), 2013)
The role of marks in the era of globalization of markets is very important, especially in maintaining fairbusiness competition and preventing piracy of marks that will be detrimental to the registered mark, bothdomestically and internationally. Therefore, the business requires international trademark registrationprocedures in order to obtain legal protection in both countries of origin and in other countries where theexpansion of business is required. Along with the development of international trade, the need to protectthe international brand is also getting stronger. International conventions on the protection of brands arepresent in the Paris Convention for the Protection of Industrial Property, Nice Agreement (Concerningthe International Classification of Goods and Services for the Purposes of the Registration of Marks),Madrid Agreement Concerning the International Registration of Mark and Madrid Protocol.The Madrid Protocol is an international treaty governing international trademark registration, with oneapplication, one language and one currency. The Madrid Protocol provides effective legal protection ofregistered marks and facilitates national brands into global brands able to compete with foreign marks.The ratification of the Madrid Protocol, expected to be done by the government, is a positive step insupporting the protection of domestic brands and is extensive and efficient; however, it requires goodhuman resource readiness, facilities and infrastructure such as technology to support effectiveimplementation of the Madrid Protocol in the protection of this brand.